Application of Geographic Information System (GIS) Technology to Formulate Unused Spring Water Optimization Strategy - Lisan, Ahmad Rifan Khoirul; Murdiyanto, Eko; Harsana, Minta (Universitas Ahmad Dahlan, 2024)
Background: This article presents the findings of a comprehensive community empowerment program that focused on the application of Geographic Information System (GIS) technology for the optimization strategy formulation of unused spring water. Contribution: The contribution of this program address the challenge for better utilization of unused spring water and promote sustainable water management practices. Method: The study employed GIS technology to identify and map unused springs, followed by hydrological analysis and water quality assessment to inform the development of optimization strategies. Results: This program suggested infrastructure development, water conservation measures, and distribution network design to enhance water availability. Conclusion: The findings show that GIS approach is suitable for further applications in other Indonesian mountainous villages with similarly shared community traits. However, further some locality aspects, including, but not limited to community leadership and economic power, need to be assessed further, as they play significant influences on the success of the program